Upaya Komunikasi Internal dalam Meningkatkan Kinerja Karyawan PT. Agta Sinar Jaya Bandar Lampung - Suryani Suryani; Melan Susanti; Yuli Evadianti (Departement of Mathematics Education, 2022)
The purpose of this study is to find out, understand and analyze how internal communication efforts in improving employee performance in PT. Agta Sinar Jaya Bandar Lampung which includes horizontal communication, vertical communication, and diagonal communication. The data analysis technique used is qualitative analysis with interactive models including data collection, data reduction, data presentation, and drawing conclusions. Data is collected through reference books related to internal communication and employee performance, through interviews, and field research. The result of this study is that internal communication in the vertical dimension occurs in the company PT. Agta Sinar Jaya Bandar Lampung is a tiered and systemized communication, causing a lack of openness, the delivery of ideas and ideas to improve employee performance is hampered because it has to go through the bureaucratic process of the company's organization. In the application of horizontal communication, internal communication programs in an effort to improve employee performance at PT. Agta Sinar Jaya Bandar Lampung has not been optimally implemented, such as the lack of space and time available for discussions between fellow employees, sharing information and supporting each other between employees. Meanwhile, diagonal communication in PT. Agta Sinar Jaya Bandar Lampung is still rare, because the communication applied to the company is tiered communication, so diagonal communication only occurs when it is a complex problem that must involve the leadership and solve the problem that occurs.